Analysis of Vilanalysis of Mental Readiness for Early Marriage in Ciamis Regency - Shofi Ghusfathin; Yandi Cahya Yundani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to reduce the increasing rate of early marriage in Ciamis Regency. The research employs a qualitative method, conducting interviews at the Ciamis Religious Court with prospective brides and grooms applying for marriage dispensations. Data analysis was performed to understand the mental readiness of adolescents regarding early marriage. The findings indicate that the mental readiness of marriage dispensation applicants is at a threshold between ready and unready. Many young couples are still trapped in the adolescent developmental phase, where the need for immediate gratification outweighs long-term planning. This is evident from the reasons for marriage, which are often triggered by economic factors, education, and unintended pregnancy, without due consideration for the mental and emotional preparedness required to face domestic conflicts. These findings support the understanding that marriage is not merely about the solemnization of the ijab Kabul but necessitates comprehensive mental and financial readiness.